Kestabilan emosi di kalangan staf dan pelajar Fakulti Pendidikan, UTM [electronic resource] = Emotional stability amongst staff and students of Faculty of Education, UTM - 238164 Mohamed Najib Abdul Ghafar; Yusof Boon, 1964-; Azizi Yahaya (Skudai : Universiti Teknologi Malaysia, 2002)
32